Sharpening Students' Racial Literacies through Multimodal Subversion. Issue 2 (31st July 2022) - Howell, Emily; Dyches, Jeanne
Abstract: This case study shares the experiences of 24 students in an urban high school in the U.S. Midwest who spent 6 weeks learning about, and applying tenets of, critical race theory (CRT) to their analysis of the canonical The Adventures of Huckleberry Finn . Students created a visual essay reflecting their understanding of CRT in the novel and in their broader social milieu. Drawing from, and sharing possibilities for, merging theoretical principles from CRT, multiliteracies, and the writing process, we/the authors ask: How can students utilize multiple perspectives to sharpen racial literacies through multimodal design? These findings include three points of integration: (a) overt instruction, Whiteness, and organizing; (b) critical framing, intersectionality, and address; and (c) transformed practice, critical stance, and revise and survey again.